Bride wealth in marriage: the case of Uang Panai in South Sulawesi, Indonesia - ., Nurmiati; Mohamad Diah, Nurazzura (School of Social Sciences, Universiti Sains Malaysia (USM), 2017)
Bride wealth is the amount of substantial resources such as money, property and other forms of wealth that is given to the bride’s family by the groom. Recently, bride wealth has become a significant issue particularly for the marriage age in many rural countries. In this paper, the researchers analyze 20 articles to look for cross-cultural interpretations and practices about bride wealth in two ways 1) describing the importance of bride wealth and 2) defining factors that stipulate the amount of bride wealth among various cultures. The researchers conducted a summative content analysis to see variations of bride wealth practices across countries. The analysis suggests that culturally, the groom is bound to provide the bride wealth to his future wife. Although it is not grounded in religion, bride wealth is compulsory to legalize marriage, enhance social stratification, and maintainfamily stability as well as cultural identity. Various factors are regarded as significant in whichthe amount of bride wealth is stipulatedfor instance educational level, economic standing, family stratification and physical appearance. Indeed, bride wealth is crucial in one’s marriage and it has an important role in many societies. It will maintain as an important tool that perpetuates culture and tradition. However, very limited studies haveaddressed the impacts of bride wealth on women’s health and wellbeing.Finally, the paper suggests for more interdisciplinary studies into the modern practice of bride wealth in order to find new ways of fulfilling one’s cultural obligation due to the fact that there are changes in the society today which challenged the relevance of bride wealth practice.